First-Year Programming Students: Perceptions of Their Tertiary Learning Environment - Crump, Barbara Jill (Curtin University, 2002)
The purpose of this research was to investigate first-year tertiary programming students' perceptions of their learning environment, based on the subgroups of gender and "new arrivals" (immigrant and international students of diverse nationalities, culture and educational backgrounds). The literature provides strong evidence that the nature of the learning environment for females studying computing can be uninviting and may be influential in the low rates of female enrolments and retention compared with males. Studies indicate that the cultural norms and artefacts of computing, the minority status of women in computing courses, attitudes, language, experience and institutional context all contribute to a learning environment that proves unattractive and can be detrimental for some women. In recent years, there has been an increased enrolment by New Zealand educational institutions of new arrival students. Research suggests that new arrival students, who leave their home country to live and study in a foreign land, experience difficulties in their learning environment and often have problems adjusting to living and studying in their host country. This research used a mixed-method design to investigate first-year computer programming students' perceptions of their learning environment at three tertiary institutions in Wellington, New Zealand. A survey, the College and University Classroom Environment Inventory (CUCEI), was completed by 239 students, yielding quantitative data about students' perceptions of their Actual and Preferred learning environment. In addition, 28 students, selected to represent gender and new arrival subgroups, participated in interviews and 11 hours of observation were conducted in programming classrooms.The findings from the survey indicated that students perceived their learning environment with some satisfaction but they suggested improvements relating to the innovation and individualisation dimensions of their learning environment. The perceptions of the student subgroups, defined by gender and as new arrivals were investigated. Although the findings from multivariate analysis of variance of the CUCEI results did not identify differences between the subgroups the interviews revealed wider equity issues and concerns that highlighted differences amongst students of the sex and origin subgroups. Recommendations, based on the study's findings, include suggestions to improve institutional policy relating to the organisation of teaching practice and some cautions about the further use of the survey. The findings have important implications for creating a more equitable and positive learning environment for all students.